A surface-reactive high-modulus binder for the reversible conversion reaction of nanoparticular cobalt oxide. (20th January 2017) - Lee, Myeong-Hee; Kim, Tae-Hee; Hwang, Chihyun; Kim, Jieun; Song, Hyun-Kon
Abstract: Conversion-reaction-based anode materials for lithium ion batteries (LIBs) such as transition metal oxides have been considered as high-capacity alternatives to graphite. In the conversion reactions, interestingly, microparticles have been known to be superior to nanoparticles in terms of capacity retention along repeated cycles. In this work, a cross-linked two-component binder system of poly(acrylic acid) and carboxymethyl cellulose (PAA/CMC) was used for nanoparticular Co3 O4 . The binder was characterized by high modulus and strong bonding to the surface oxide of Co3 O4 . Even without carbon coating, the composite electrodes of nanoparticular Co3 O4 in the presence of PAA/CMC showed significantly enhanced cycle retention with improved reversibility of the conversion reaction.